Efficient Spin Injection Through Exchange Coupling at Organic Semiconductor/Ferromagnet Heterojunctions - Zhan, Yiqiang; Holmström, Erik; Lizárraga, Raquel; Eriksson, Olle; Liu, Xianjie; Li, Fenghong; Carlegrim, Elin; Stafström, Sven; Fahlman, Mats (Advanced materials (Weinheim), 2010)
The schematic visualization of the Alq3 moleculeon the Fe substrate with the optimized geometry at lowest total energy. When the Alq3 molecule is relaxed on the surface, only two of the wings are lying down on the Fe surface, and the third wing remains perpendicular to the surface, showing a strong hybridization occurance.